2004
DOI: 10.1614/ws-03-007r1
|View full text |Cite
|
Sign up to set email alerts
|

Spring wheat seed size and seeding rate effects on yield loss due to wild oat (Avena fatua) interference

Abstract: The development of competitive cropping systems could minimize the negative effects of wild oat competition on cereal grain yield, and in the process, help augment herbicide use. A 3-yr field experiment was conducted at Kalispell, MT, to investigate the effects of spring wheat seed size and seeding rate on wheat spike production, biomass, and grain yield under a range of wild oat densities. Wheat plant density, spikes, biomass, and yield all increased as seed size and seeding rates increased. Averaged across a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 28 publications
5
37
0
1
Order By: Relevance
“…As expected, barley stand density increased while tillers plant −1 decreased at the higher seeding rate (Table 4); but stand density as a function of seeding rate was higher at the lower (68%) compared to the higher (58%) rate. Th is eff ect of seeding rate has been documented previously in barley (Jedel and Helm, 1995) and wheat (Triticum aestivum L.) (Stougaard and Xue, 2004) and is likely due to increased intrarow competition at the higher seeding rates with a subsequent increase in seedling mortality.…”
Section: Effect Of Seeding Ratementioning
confidence: 73%
“…As expected, barley stand density increased while tillers plant −1 decreased at the higher seeding rate (Table 4); but stand density as a function of seeding rate was higher at the lower (68%) compared to the higher (58%) rate. Th is eff ect of seeding rate has been documented previously in barley (Jedel and Helm, 1995) and wheat (Triticum aestivum L.) (Stougaard and Xue, 2004) and is likely due to increased intrarow competition at the higher seeding rates with a subsequent increase in seedling mortality.…”
Section: Effect Of Seeding Ratementioning
confidence: 73%
“…Also, the highest kernel yield was achieved with sowing rate 600 germinable seeds m -2 (Kristó et al, 2007;Maric et al, 2008). On the other hand, various sowing rates had highly significant influence on the number of fertile tillers (Khaliq et al, 1999;Chaudhry and Hussain, 2001;Wajid et al, 2004), and that sowing rate influences mainly of number of spikes per square meter, which has the closest relationship to yield from all yield components (Spink et al, 2000;Guberac et al, 2000;Lloveras et al, 2004;Stougaard and Xue, 2004;Guberac et al, 2005;Lithourgidis et al, 2006;Ozturk et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…High seeding density has been reported to improve grain yield of wheat under conventional cropping systems (Conventry et al, 1993;Rurnett et al, 2003). Stougaard and Xue (2003) found that high seeding density increased yield 12%-18% when compared with low seeding density in Montana. Work in Canada showed that a 60 kg ha −1 seeding rate resulted in a 61% higher plant density than a 30 kg ha −1 seeding rate (McLeod et al, 1995).…”
Section: Seeding Densitymentioning
confidence: 91%